Evaluation of the impact of ultraviolet B radiation on the epidermal barrier - Postrzech, Katarzyna; Welz, Kalina; Kopyra, Joanna; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Ultraviolet radiation (UV) causes various adverse effects on skin, such as burns and premature skin aging, and contributes to the development of skin cancer. Objective. To assess the impact of UV-B on the structure and function of stratum corneum. Material and methods. The study group comprised 20 volunteers (14 women and 6 men) aged from 18 to 71 years (median: 48 years). Skin phototype was identified in each patient with Fitzpatrick’s scale. Every patient underwent phototesting using the TH-1-Skintest kit (Cosmedico Medizintechnik GmbH, Trossingen, Germany) equipped with PL12 lamps (Philips, Eindhoven, The Netherlands) emitting a broad UV-B spectrum (280-320 nm) with intensity of 3.2 mW/cm². Patients were exposed to various UVB doses (5-30, 9-50 or 14-80 mJ/cm²) depending on the skin phototype. The minimal erythema dose (MED) was determined 24 hours after irradiation as well as the measurements of electric impedance of stratum corneum and transepidermal water loss in exposed and unexposed areas. Statistical analysis was performed using the Friedman ANOVA test and paired Student t-test. Results. MED ranged from 20 to 52 mJ/cm² (median: 25 mJ/cm²). The values of electrical impedance of the skin exposed to 1 MED UVB ranged from 18.8 to 57.5 AU (median: 34.4 AU) and did not differ significantly from the electrical impedance of the unexposed area (range: 21.1-57.9 AU, median: 39.0 AU, p = 0.2). Similarly, transepidermal water loss was not significantly affected by UVB in areas exposed to 1 MED (range: 0.9-19.9 g/m²/h, median: 6.8 g/m²/h) compared to unexposed skin (range: 1.1-12.2 g/m²/h, median 7.8 g/m²/h, p = 0.26). Moreover, UVB doses up to 1.5 MED also did not significantly influence the integrity of the stratum corneum. Conclusions. UVB radiation in doses up to 1.5 MED does not directly damage the stratum corneum of the epidermis.